The Effect of Snake Fish Extract (Channa striata) on Post Cesarean Section Wound Status in Postpartum Anemia Mothers - Fajri, Umi Nur; Hadisaputro, Suharyo; Soejoenoes, Ariawan (Indonesian Journal of Medicine, 2018)
Background: A labor with Sectio Caesarea (SC) will increase mortality rate, which is twice the rate of vaginal delivery. The morbidity rate is also higher in SC delivery due to post-SC wound infection. Post-SC wound healing requires high albumin. This study is intended to determine the effect of snake fish extract on post-SC wound status in postpartum anemia women.Subjects and Method: This was a true experimental study with randomized control group post-test design. The study was conducted at Hj. Anna Lasmanah Hospital, Banjarnegara, Central Java, in May to June 2018. The population of all post-partum postpartum mothers was anemia. A sample of 30 study subjects was selected by stratified random sampling, consisted of 15 study subjects in intervention and control groups. The dependent variable was post-SC wound. The independent variable was snake fish extract. Post-SC wound was measured by REEDA scales. The data was analyzed by General Linear Model Repeated Measure.Results: In day-5, post-SC wound in the intervention group (mean= 0.27; SD= 0.46) was lower than control group (mean= 1.07; SD= 0.80) and it was statistically significant (p= 0.002).Conclusion: Channa striata extract can accelerate post-SC wound healing.Keywords: Channa striata extract, wound status, sectio caesarea, anemiaCorrespondence:Umi Nur Fajri. Applied Midwifery, Graduate Program, School of Health Polytechnics, Ministry of Health Semarang. Email: nurfajriumie@yahoo.co.id. Mobile: 085214594590.Indonesian Journal of Medicine (2018), 3(2): 84-88https://doi.org/10.26911/theijmed.2018.03.02.04